Tax compliance behavior of taxpayers in Ethiopia: A review paper - Esmael Abdu; Mohammd Adem (Cogent Economics & Finance, 2023)
This review paper attempted to assess the tax compliance behavior of taxpayers in Ethiopia. The objectives were specifically to identify determinants and challenges of tax compliance behavior of taxpayers in Ethiopia. Taxes are the most important sources of the government that make it possible to finance infrastructure, investment, and the provision of services for citizens. Tax compliance involves being aware and complying with tax laws and regulations set by the government and tax authorities. Tax non-compliance is an unwillingness in obeying tax laws and regulations. Tax non-compliance has been a challenge to the government and tax authorities in collecting as much tax as required for the nation. Failure to comply with tax prevents adequate revenue collection of the state. The major challenges of tax compliance in Ethiopia are the complexity of the tax system, inefficiency of tax authorities, lack of tax knowledge and awareness, negative perception of taxpayers, a negative act of tax assessors, absence of tax training, lack of transparency of tax system, arbitrary estimation of taxes, personal financial constraints, political instability and lack of timely tax audit.
Keywords: 330; Ethiopia; tax; tax compliance; tax non-compliance; taxpayers